STRUKTUR BATIN DAN FUNGSI MANTRA MASYARAKAT BESEMAH KOTA PAGAR ALAM - Oktavia, Tasya (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2024)
The Mantra of the Besemah community is one of the cultural assets that needs to be preserved. However, the spell is currently threatened with extinction. This is caused by several factors, namely the reduced interest of the community, especially young people, to learn spells. Getting older and the death of the chanters, not a few have even died, as well as the lack of documentation regarding the spell. This study aims to analyze the inner structure and function of the mantras of the Besemah community. This study uses qualitative research methods with data collection techniques through interviews and literature studies. The results of the study show that the mantras of the Besemah community have an inner structure consisting of four parts, namely theme, (feeling), tone and message.